2003
DOI: 10.1016/s0167-4889(03)00027-2
|View full text |Cite
|
Sign up to set email alerts
|

Human serum albumin and its structural variants mediate cholesterol efflux from cultured endothelial cells

Abstract: In the present study, we used the human EA.hy926 endothelial cell line as the model system to investigate the effect of human serum albumin (HSA) and its structural variants on cholesterol efflux. Initial studies showed that HSA promoted cholesterol efflux in a dose- and time-dependent manner, reaching a plateau at 10 mg/ml at 90 min. As a control, gelatin displayed no significant effect on efflux, while HSA was significantly more efficient than ovalbumin and bovine serum albumin (BSA) in promoting cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
0
28
0
3
Order By: Relevance
“…It is also interesting to note that other investigators recently noted recombi-nant human albumin can serve as cholesterol acceptor and showed that several site-specific mutations can significantly reduce the cholesterol acceptor activity of the protein. 14 It is important to note that we observed different sources of human serum albumin had significantly different cholesterol acceptor activity, suggesting that a conformationally intact albumin is needed for full cholesterol acceptor activity.…”
Section: Discussionmentioning
confidence: 75%
“…It is also interesting to note that other investigators recently noted recombi-nant human albumin can serve as cholesterol acceptor and showed that several site-specific mutations can significantly reduce the cholesterol acceptor activity of the protein. 14 It is important to note that we observed different sources of human serum albumin had significantly different cholesterol acceptor activity, suggesting that a conformationally intact albumin is needed for full cholesterol acceptor activity.…”
Section: Discussionmentioning
confidence: 75%
“…The function of serum albumin in cholesterol transfer between fibroblast cells and lipoproteins is well studied, as it is for endothelial cells, due to its central role in coronary vascular disease and atherosclerosis (Zhao and Marcel 1996; Ha et al 2003). This is an important function for albumin in many cell types and particularly for cholesterol dependent cell lines such as NS0 myeloma and derivative hybridoma cells.…”
Section: Binding Of Ligands and Carrier-function Of Albumin In Culturmentioning
confidence: 99%
“…HDL-like particle is assembled as a disk particle composed of phospholipid and unesterified cholesterol by ABCA1-helical apolipoprotein interaction Jayaraman et al, 2011). However, cholesterol by itself does not form lipid-protein complex particles with apolipoprotein, though it may directly bind to some proteins such as serum albumin (Ha et al, 2003;Peng et al, 2008). To the contrary, physicochemical assembly of the HDL-like particles, similarly to those produced by the ABCA1-mediated cell-apolipoprotein interaction may not essentially require cholesterol (Fukuda et al, 2010;Jayaraman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%